The impact of export promotion institutions on trade: Is it the intensive or the extensive margin? - Christian Volpe Martincus; Jerónimo Carballo; Andrés Gallo (Inter-American Development Bank (IDB), 2010)
This paper provides evidence on the channels through which export promotion institutions affect bilateral trade using a sample of Latin American and Caribbean countries over the period 1995-2004. We find that these institutions have a larger impact on the extensive margin of exports, especially in the case of trade promotion organizations.
hdl:11319/3191
Keywords: F13; C23; 330; Export Promotion; Trade Margins; Latin America